STRUCTURE OF ENGLISH BUSINESS MONOMIALS - Чайка, Оксана; Бамбура, А (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
The given article presents the analysis and description of the structure assoctiated with business monomials in the English terminology. The research carries on to the breakdown of the English business monomials that fall under three groups, i. e. English business monomials that consist of one term only, English business monomials that include two terms (components), English business monomials that comprise more than two terms and variables in the structure. The two classifications in both algebra and applied linguistics – general as to monomials and polynomials and the English business monomials – are richly exemplified with certain algebraic expressions and the English fixed terminological set expressions introduced as business monomial / polynomials. Рurpose. The term of business monomial is introduced to communicate the need in differentiation between the term itself and a business term that may consist of a number of terms as components in a term. In addition, to advance a rather technological view for further research and computer-aided linguistics the relevant classification is proposed as based on the similarities found between the algebraic expression, its components (terms and variables) and the fixed terminological set in the business context, its components, respectively. Methods. Contrastive analysis, mathematical logic (algebraic), description, as well as integration methodology, which involves logical, component, word-forming analysis of the business monomial structure. Results. The paper presents the classification of algebraic expressions as based on their structure and that of the business monomials in the English business setting. The research carried out allows for in-depth study of the terminological set expression in Business English with the break-out of the terms / components of the business monomial in English. Term composition is enabled with morphological and syntactical derivational tools, which further unveils into the study and description of simple and compound / complex monomials. Such may consist of (I) a mono-term (one word unit that makes a simple business monomial), (II) bi-term monomial (two elements that are viewed as a single terminological set expression), (III) poly-term monomial (three and more elements to present the fixed set expression in business) as opposed to binomials and polynomials in general. Originality. The new term of business monomial is introduced to differentiate the term in applied linguistics and in language for specific purposes, in particular, and the monomial / polynomial in the English business context. The structure of the business monomial is compared with that of the algebraic expression in mathematical logic subject to the similarities found in the structure and inter-relations between the terms of the expression. Conclusion. The study carried out presents a scientific challenge for further research and reviews, more illustrations may allow for in depth plunge and more findings that may definitely contribute to the contemporary linguistics, applied linguistics, in particular.